Towards an increasing awareness and use of remote sensing and geographical information systems in veterinary medicine in Nigeria (2003)
Although Remote Sensing (RS) and Geographical Information Systems (GIS) have been employed for decades for diseases surveillance, prediction and intervention programs, its awareness and application to Veterinary Medicine in Nigeria is a recent phenomenon. Over the past couple of years, a number of veterinarians at the Department of Veterinary Public Health and Preventive Medicine, University of Ibadan. Ibadan. Nigeria base pioneered the use of GIS to study the Epizootiology of Trypanosomosis. African swine fever, Tuberculosis and Transhumant Pastoralism in Nigeria. This has been in collaboration with GIS personnel in the University's Department of Geography and the private sector. At Government level, the Federal Depot Uncut of Agriculture and Rural Development recently sponsored five veterinarians (including the author) in the first leg of an intensive training on the application of CIS to Veterinary Epidemiology. The intensive four week course took place at the Regional Center for Aerospace Survey (RECTAS), Ile-lfe, Nigeria, and is part of the capacity building aspect of the Nigeria component of the Pan African Program for the Control of Epizoonics (PACE). RS/GIS is not vet in the curricula of any of Nigeria's five (5) veterinary schools, neither is there as vet any unit/center devoted to the application of RS/GIS to veterinary Medicine in Nigeria. Although the theme of in 2004 Congress of the Nigerian Veterinary Medical Association was ADVANCES IN INFORM ATION TECHNOLOGY: IMPACT ON THE VETERINARY PROFESSION, only one paper (by the author), dealt with the application of RS/GIS to Veterinary Medicine. To promote increased awareness and use of RS/GIS in Veterinary Medicine, multilateral assistance will he required in the training of personnel and equipping of Veterinary RS/GIS units.